2021
DOI: 10.1111/acps.13261
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year mortality of severely malnourished patients with chronic anorexia nervosa admitted to a medical unit

Abstract: Objective Anorexia nervosa (AN) is associated with one of the highest mortality rates of any psychiatric disorder but limited mortality data were reported for those with extremely severe malnutrition. This study aimed to estimate standardized mortality ratio (SMR), investigate predictive factors of mortality and causes of death among a sample of patients with AN admitted to a specialized clinical nutrition unit (CNU) because of extremely severe malnutrition. Methods Between 11/27/1997 and 01/15/2014, vital sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 43 publications
(134 reference statements)
5
39
0
2
Order By: Relevance
“…The association between malnutrition (body mass index, the restrictive type of anorexia nervosa, and duration of illness) and hematological de ciencies in our study is consistent with previous reports [2,3,5,8,9], although these previous studies did not control for potential cofounding factors. What was not previously known is that this relationship further applies to the hematological values during the refeeding period, in which the lowest hematological cell measures are observed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The association between malnutrition (body mass index, the restrictive type of anorexia nervosa, and duration of illness) and hematological de ciencies in our study is consistent with previous reports [2,3,5,8,9], although these previous studies did not control for potential cofounding factors. What was not previously known is that this relationship further applies to the hematological values during the refeeding period, in which the lowest hematological cell measures are observed.…”
Section: Discussionsupporting
confidence: 93%
“…Pancytopenia, a decline in all three hematological measures, is also occasionally found in anorexic patients, and its frequency was reported to be 23% among anorexic patients with severe malnutrition [2]. Indeed, anemia is considered one of the predictors of mortality for anorexic patients; the 5-year mortality rate for anorexic patients with severe undernutrition is 11.5%, and their mortality risk is 15 times higher than that in the general population [5]. Regarding life expectancy, Harbottle et al estimated that a woman who has had anorexia nervosa since 15 years of age is likely to live 25 years less than predicted for the normal population [6].…”
Section: Introductionmentioning
confidence: 99%
“…an almost 6 times increased risk. In a recent study, after 5 years follow-up the SMR of anorexia nervosa inpatients with (complications of) severe malnutrition was found to be as high as 15.9 (95% CI 11.6–21.4) [ 51 ]. This study population was probably more severely affected than most of the study populations included in the meta-analysis [ 50 ].…”
Section: Incidencementioning
confidence: 99%
“…Evidence has shown that mortality in EDs is influenced by age, sex, and case severity [6,9,16,44]. Generally, older individuals have an elevated risk of mortality for all types of EDs compared to the mortality of younger individuals [8], probably reflecting the strong effect of age and chronicity of illness on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These disorders encompass a range of problematic behaviors, including starvation, binge eating, and purging, leading to an increased risk of premature death [4]. Many factors in these patients have also been identified as predictors of mortality, such as type of ED diagnosis, low body mass index (BMI), suicide behaviors, alcohol abuse, and comorbidities [5][6][7]. In addition, the age of onset and age of treatment are also two important death-predictive factors in patients with EDs, as evidence has shown that older individuals (25-44 age group) have an elevated risk of mortality for all types of EDs compared to youth (15-24 age group) [8].…”
Section: Introductionmentioning
confidence: 99%